Asphyxia as a Risk Factor for Neonatal Hypoglycemia - Mufidati, Luthfina; Anggraini, Alifah; Wibowo, Tunjung (Journal of Nepal Paediatric Society, 2018)
Introduction: Hypoglycemia leads to brain developmental disturbances and abnormality on its function. Perinatal stress including asphyxia is a significant cause of neonatal hypoglycemia, thus, it is important to prevent it by controlling its relevant confounding variables. The aims of this study were to identify the risk factors of neonatal hypoglycemia and its related variables, focusing on the role of asphyxia in neonatal hypoglycemia. Material and Methods: We conducted a nested case control study using a cohort data from South East Asia Regional Neonatal-Perinatal Database year 2013 of the Maternal and Perinatal Unit, Dr. Sardjito General Hospital Yogyakarta. We randomly selected neonatal hypoglycemia as a case and neonatal without hypoglycemia as a control group. We identify the risk factors from the cohort data. Logistic regression analyses were performed to investigate the association between hypoglycemia and risk factors. Results: A total of 1563 newborns were recruited in this study. Five hundred and twenty newborns were excluded due to incomplete data and major congenital anomalies. By simple randomization sampling, we selected 52 newborns in cases group and 104 newborns in control group. In multivariate models, being asphyxia, low birth weight (LBW), large for gestational age (LGA), and early onset of neonatal sepsis showed significant effects on risk of hypoglycemia, OR= 2.8 (95% CI: 1.01 – 7.80), OR 7.1 (95% CI 1.54-32.37), OR 37.2 (95% CI 6.28-219.85), and OR 40.6 (95% CI 10.84-152.01), respectively. Conclusion: Asphyxia, LBW, LGA and early onset neonatal sepsis were significant risk factor for neonatal hypoglycemia.